Analisis Komparatif Laporan Arus Kas Dalam Menilai Tingkat Likuiditas Pada PT Indosat Tbk. Periode 2009 – 2014 (Studi Empiris Pada Perusahaan Telekomunikasi Yang Terdaftar Di BEI) - R. Aditya Kristamtomo Putra; Heikal Muhammad Zakaria (Accounthink, 2016)
Companies have to publish cash flow statement in annual reporting because cash flow information as analyses tool of company performance for information users. The aim of this research is to find out and to evaluate the level of financial liquidity ratio, to reveal the role of cash flow information in measuring financial performance of PT. Indosat Tbk. PT Indosat Tbk. is a telecommunication company listed in Indonesian Stock Exchange (IDX) yang merupakan perusahaan telekomunikasi yang terdaftar di Bursa Efek Indonesia. The data used is primary data like company’s financial statement. Data collection procedure used is literature review namely data collecting method from various information sources associated with cash flow statement analyses and financial statement analyses. The research results show that financial cash flow liquidity ratio of PT. Indosat Tbk. quite good and stable from 2009-2014. However, in 2009 ratio below the limit (dissatisfactory).